Analyzing the Impact of Information Systems Digitalization on Organizational Performance through the Technology Acceptance Model (TAM) - Sitompul, Novian Paisal; Haqki, Bay; Harahap, Baginda; Harahap, Solianna; Panggabean, Erwin (Journal of Technology and Computer, 2026)
The digitalization of information systems has become a key strategy for organizations seeking to improve operational efficiency, decision-making quality, and overall organizational performance. However, the successful implementation of digital technologies depends largely on users’ acceptance and willingness to adopt such systems. This study aims to analyze the impact of information systems digitalization on organizational performance using the Technology Acceptance Model (TAM). The research examines the relationships between perceived usefulness, perceived ease of use, user acceptance, and organizational performance. A quantitative research approach was employed by collecting data through structured questionnaires distributed to employees who actively use digital information systems within their organizations. The collected data were analyzed using Structural Equation Modeling (SEM) to evaluate the proposed research model and test the hypotheses. The findings indicate that perceived usefulness and perceived ease of use significantly influence user acceptance, which subsequently contributes to improved organizational performance. These results highlight the importance of designing user-friendly and beneficial digital information systems to maximize organizational outcomes. The study provides valuable insights for organizations in developing effective digital transformation strategies and enhancing sustainable organizational performance through technology adoption.